Potential Antimetastatic Effect of Timosaponin AIII against Human Osteosarcoma Cells through Regulating the Integrin/FAK/Cofilin Axis - Yi-Hsien Hsieh; Wen-Hung Hsu; Shun-Fa Yang; Chung-Jung Liu; Ko-Hsiu Lu; Pei-Han Wang; Renn-Chia Lin (MDPI AG, 2021)
Timosaponin AIII (TSAIII) is a steroidal saponin which demonstrates anti-tumour activities. However, the effect of TSAIII on human osteosarcoma cells remains largely unknown. In this study, we demonstrated that TSAIII exerted a significant inhibitory effect on the distribution of cytoskeletal F-actin and cytoskeletal-related proteins, which contributed to the suppression of cell migration and invasion, without inhibiting cell growth or apoptosis. In the synergistic inhibitory analysis, cotreatment of TSAIII with αVβ3 integrin inhibitor [Cyclo(RGDyK)] or focal adhesion kinase (FAK) inhibitor (PF-573228) exerted greater synergistic inhibitory effects on the expression of Intergin αVβ3/FAK/cofilin axis, thus inhibiting the migration and invasion capacities of human osteosarcoma cells. TSAIII was demonstrated to significantly inhibit the pulmonary metastasis formation of human osteosarcoma cells in vivo in metastasis animal models. These findings reveal the inhibitory effects of TSAIII on the metastasis progression of human osteosarcoma cells and the regulation of integrin-αVβ3-FAK-Src and TESK1/p-cofilin mediated cytoskeletal F-actin pathway. Therefore, TSAIII might represent a novel strategy for the auxiliary treatment of human osteosarcoma cells.